Proposed marketing strategy for cv karya reksa informatika - Nur Ilman, Nabil; Furinto, Asnan (The Indonesian Journal of Business Administration, 2018)
Abstract - CV Karya Reksa Informatika is a company that carries out its work specifically for IT solutions and consulting services such as website development, mobile development, system integration, enterprise information systems, and other IT needs. CV Karya Reksa Informatika was initially established in 2016 in Sidoarjo - Surabaya.As a relatively new player, CV Karya Reksa Informatika does not have yet a marketing strategy. After 2 years running, CV Karya Reksa Informatika only relies on the relation to get new project, in the future it will be bad for the company. Through analysis of both internal and external generated, tight competition in the industry make CV Karya Reksa  Informatika should searching for new way in order to have a good portfolio and gain sustainable competitive advantage.To support this new strategy, the mobile site will also develop which will be developed by CV Karya Reksa Informatika. In the new site contains elements that correspond to the strategies and components used by providing suitableinformation to accommodate potential customers who visiting for information related to website development, mobile applications, and system integration. Kerwords: IT business, marketing strategy, business strategy, software industry, website